Decellularized rat brain extracellular matrix effectively induces the dopaminergic differentiation of human adipose-derived stem cells - Hossein Faghih; Arash Javeri; Masoumeh Fakhr Taha (PLoS ONE, 2025)
The extracellular matrix (ECM) plays essential roles in regulating various aspects of nervous system development. The ECM can be obtained through decellularization techniques, which preserve the native structure of tissue while removing cells and genetic material. Despite recent advancements in decellularization methods, removing cells from brain tissue remains challenging due to its delicate mechanical structure. Moreover, previous studies have not specifically evaluated the impacts of decellularized brain ECM on dopaminergic specification of stem cells. Here, we decellularized rat brain sections using a combination of chemical and enzymatic factors. Successful decellularization of sections was confirmed by DAPI, Haematoxylin and Eosin and Masson’s trichrome staining, laminin immunostaining, DNA content analysis, and scanning electron microscopy. The sections were then recellularized with human adipose tissue-derived stem cells (hADSCs) and subjected to dopaminergic differentiation using a combination of growth factors. Some ADSCs were also differentiated in gelatin-coated tissue culture plates, employing a conventional two-dimensional culture method. After 12 days, the differentiated cells in both conditions expressed certain neuronal markers, especially those related to dopaminergic differentiation. However, GLI1, VMAT2, GIRK2, and TH genes, as well as NEFL, FOXA2, LMX1A, and TH proteins were upregulated in the ADSCs differentiated on decellularized sections. Furthermore, DDC and CALB were exclusively expressed by the ADSCs on decellularized brain sections. Overall, our findings indicated the significance of decellularized brain ECM to serve as an effective bioscaffold for dopaminergic differentiation of hADSCs. This highlights the importance of decellularization techniques for the advancement of midbrain tissue engineering and regenerative medicine for Parkinson’s disease in the future.